An Analysis on the Dual Role of Working Mothers in the Era of Pandemic Covid-19 - Cahyanti Puspaningsih (LEGAL BRIEF, 2022)
The Covid-19 pandemic has suddenly changed the order of life of the global community. One of them is the family environment, where working mothers experience an increased dual role while at home. This study aims to analyze the dual role strategies of working mothers in the midst of the Covid-19 pandemic. This type of research is qualitative research using a case study approach. The results show that the Covid-19 pandemic has caused changes in the family environment. Working mothers not only experience an increase in workload, but also an increased risk of emotional disorders such as stress or fatigue due to activities everything is done at the same time as the impact of the implementation of work from home and study from home which makes home the main basis for its implementation. The dual role strategy of working mothers to deal with these conditions is to divide roles with husbands, apply a priority scale by compiling detailed items work systematically, and rearrange or reschedule all activities carried out while at home.